Herstellung prozessangepasster Halbzeuge mit variabler Blechdicke durch die Anwendung von Verfahren der Blechmassivumformung - Opel, Simon (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2013)
The central objective of this work is the manufacturing of process adapted semifinished products with a variable sheet thickness by sheet-bulk metal forming. The properties of the semi-finished products are locally adapted by the application of the forming processes upsetting, orbital forming and rolling. Furthermore the potential for the use has been evaluate